2009
DOI: 10.2217/pgs.09.113
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Model of Retinoic Acid-Induced Dyslipidemia and Insulin Resistance

Abstract: SHR-Lx displayed substantially greater sensitivity to a number of all-trans retinoic acid-induced metabolic dysregulations compared with SHR, resulting in impairment of glucose tolerance, increased visceral adiposity, and substantially greater increase of circulating triglyceride concentrations, accompanied by a shift towards their less favorable distribution into the lipoprotein fractions. These observations closely mimic the common side effects of retinoid therapy in humans, rendering SHR-Lx an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…RA is a small molecule that can easily pass through the cell membrane, being subsequently transported to the nucleus by cellular RA-binding proteins where it binds the nuclear receptors, retinoic acid receptors (RARs) (19,20). However, complicating the effects of RA on lipid metabolism, a study reported that RA increased adiposity in rats (27) and other cell line studies have shown that RA increased the differentiation of adipocytes (28,29). Levels of RA are regulated by its production via this process or degradation by CYP26 enzymes (21).…”
mentioning
confidence: 99%
“…RA is a small molecule that can easily pass through the cell membrane, being subsequently transported to the nucleus by cellular RA-binding proteins where it binds the nuclear receptors, retinoic acid receptors (RARs) (19,20). However, complicating the effects of RA on lipid metabolism, a study reported that RA increased adiposity in rats (27) and other cell line studies have shown that RA increased the differentiation of adipocytes (28,29). Levels of RA are regulated by its production via this process or degradation by CYP26 enzymes (21).…”
mentioning
confidence: 99%
“…The role of RA, a more oxidized retinoid produced from RAL, in lipid metabolism is controversial. RA used clinically is known to induce hypertriglyceridemia (25,26). Two lipogenic genes, SREBP-1 and FAS, were induced in hepatic cells by all-trans-RA in vitro (27), whereas they were dramatically suppressed in vivo (28).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were drawn after overnight fasting from the tail vein. Using high performance liquid chromatography (HPLC), triglyceride (TG) and cholesterol (C) concentrations in 20 lipoprotein fractions and the size of major classes of lipoprotein particles were determined as described previously [9] , [22] . Then the rats were sacrificed and the weights of heart, liver, kidneys, adrenals, epididymal and retroperitoneal fat pads were determined.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies identified genetic polymorphisms contributing to variation in lipoprotein diameters in distinct geoethnic groups [6] , [12] or patterns of lipoprotein subfraction distribution [13] [16] . As the TG and C content across the lipoprotein spectrum is substantially influenced by both genetic factors and environmental effects including diet [17] [19] and medication [20] [22] , mammalian models have been successfully used for reduction of complexity in the detailed analyses of their genetic determinants [23] , [24] . Already in 1996, an association study of the major lipoprotein subfractions was performed in 30 recombinant inbred HXB BXH strains derived from spontaneously hypertensive (SHR) and congenic Brown Norway (BN- Lx ) rat strains [25] .…”
Section: Introductionmentioning
confidence: 99%